Implementasi model pembelajaran kolaboratif dalam supervisi pendidikan untuk mendorong pertumbuhan profesional Guru - Sari, Rika Yohana; Variani, Herlin; Marsidin, Sufyarma; Rifma, Rifma (Universitas Cokroaminoto Yogyakarta, 2023)
Educational supervision aims to guide teachers in efforts to improve their skills, encourage superior learning, and provide assistance in overcoming obstacles. The aim of this research is to reveal how the application of collaborative learning strategies in educational supervision can encourage the growth of teacher professionalism. This research method uses literature analysis with a conceptual and theoretical approach. Five journals were the main references in this research. The research process involves topic selection, literature search, idea development, literature analysis, critical evaluation, and writing a literature review. The research results show that the use of collaborative learning strategies in educational supervision can enrich teacher professionalism. Collaboration between supervisors and teachers in reflecting on and correcting actions also has the potential to increase efficiency in the collaborative supervision process. Thus, collaborative supervision approaches provide an attractive option for improving teachers' professional skills.